Maritime Activities of the Demak Sultanate: Shipping and Trade Route in the Nusantara Network (1478-1546) - Maulana, Wildhan Ichzha; Cornelius Bayu Astana,; Finna Wijayanti,; Kumalasari, Dyah (Journal of Al-Tamaddun, 2024)
This study endeavours to explain the geostrategic conditions of the north coast of Java, as well as the activities and maritime policies of the Demak Sultanate. It adopts a historiographic approach comprising heuristics based on the book Suma Oriental as a primary source and other relevant secondary sources; in-depth verification and interpretation of data from various sources; and methodical historical writing. The results illustrate (1) the geostrategic conditions of the north coast of Java, which is in the middle of the Nusantara spice route, helped make Demak and other port cities an important emporium. The region is traversed by monsoon winds that support shipping activities and has abundant teak wood resources for the shipbuilding industry. (2) Demak’s maritime activities included military expeditions to conquer the Portuguese in Malacca and several important emporiums on the north coast of Java; trade expeditions to export-import various commodities; and establishing trade partnerships with other regions, especially Malacca and Maluku. (3) Raden Patah’s maritime policy included the deployment of military expeditions to conquer the Portuguese in Malacca in 1512, establishing trade partnerships with Malacca, producing Jung ships, and building port cities on the north coast of Java as important emporiums; Pati Unus mobilized a military expedition to conquer the Portuguese in Malacca in 1521 and formed the Demak-Cirebon-Palembang military alliance; and Trenggana conquered Lampung and Banten to control the pepper trade until the conquest of the Sunda Kelapa emporium under the Pajajaran kingdom.